TAWAKKAL AS A SPIRITUAL APPROACH TO OVERCOMING IMPOSTOR SYNDROME : A STUDY OF HADITH IBN HIBBAN NUMBER 731 - Amrulloh; Mustopa, Andi; Firdaus, Ahmad; Jazuli, Ahmad Syukron (LPPM UIN Syekh Wasil Kediri, 2025)
This study explores the role of tawakal in overcoming imposter syndrome from an Islamic perspective. Tawakal, which is the concept of surrendering to Allah, is considered an effective approach to managing the anxiety and feelings of inadequacy that often arise in imposter syndrome. This study investigates three aspects of tawakal, namely taslim and tafwidh aspects of tawakkal, as a holistic approach that combines spirituality with mental health. Through a qualitative study, this research shows that tawakal is not just a passive attitude, but an active process that can change the way we view ourselves and our surroundings. The application of the principles of tawakal has proven to have great potential in reducing the symptoms of imposter syndrome, giving individuals inner peace despite facing various challenges. Although some previous studies have discussed the relationship between tawakal and academic anxiety, as well as imposter syndrome with academic anxiety, research that specifically examines the role of tawakal in overcoming imposter syndrome is still rare. This study fills the void and emphasizes the need for further studies, especially in analyzing the hadith about tawakal from the sanad and matan perspectives.